2008
DOI: 10.1504/ijed.2008.021276
|View full text |Cite
|
Sign up to set email alerts
|

Can Web 2.0 applications save e-democracy? A study of how new internet applications may enhance citizen participation in the political process online

Abstract: Abstract:Increased citizen participation is a core element of both Web 2.0 applications and the concept(s) of e-democracy. This paper proposes a prospective view of how the Web 2.0 can be used in the context of e-democracy. After a review of both concepts, the main perceptions of internet users concerning their political activity on the internet are highlighted by an online survey realised in January-March 2007. Various Web 2.0 applications are then discussed in the light of VEDELs axis -information, discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 9 publications
0
28
0
5
Order By: Relevance
“…For example, early case studies from 2007-2008 split between documenting successes with tentative prescriptions for future progress, and failed implementations serving as illustrations on what not to do [2][3][4][14][15][16][17][18][19]. Case studies seemed to diminish in number in 2009, then pick up again in 2010 with far more success stories than failures.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, early case studies from 2007-2008 split between documenting successes with tentative prescriptions for future progress, and failed implementations serving as illustrations on what not to do [2][3][4][14][15][16][17][18][19]. Case studies seemed to diminish in number in 2009, then pick up again in 2010 with far more success stories than failures.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Fortunately, many understood that simply employing technology for the sake of technology would not result in greater citizen participation [14]. Similar to the "trough of disillusionment" from Gartner's Hype Cycle, some agencies soon found that Web 2.0 technologies can exacerbate false ideas and make small populations seem larger than they really are [14].…”
Section: Brief History: 2007-2008mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Unfortunately, social media users are not more politically engaged than nonusers, and those who are politically active are no better informed because of using social media (sometimes, quite the opposite can be true). 7 Moreover, politically inclined social media users are similar in terms of gender, income, and education to politically active citizens who don't use social media.…”
Section: Political Participationmentioning
confidence: 99%
“…It is argued that future Web 3.0 developments which merge semantic web technologies with social media technologies will provide great opportunities for eParticipation utilising linked data and crowdsourcing (Peristeras 2009, Bizer 2009). eParticipation initiatives can also include live chats with administrators and/or elected officials (Breindl and Francq, 2008). For example, these may take the form of online question and answer sessions arranged at specific times.…”
Section: Effective Participation: Examples Of Web 20 Tools For E-parmentioning
confidence: 99%